Synthesis, characterization, and performance evaluation of polymeric HALS in ethylene-propylene-diene terpolymer (EPDM) - Lonkar, Sunil P.; Rana, S.; Singh, R. P.; Lacoste, Jacques; Gardette, Jean Luc; Jestin, F.; Brocord, E. (Journal of Macromolecular Science, Part A: Pure and Applied Chemistry, 2005)
A polymeric hindered amine light stabilizer (HALS), wherein the hindered amine functionality was attached to the maleic anhydride graft ethylene-propylene-diene terpolymer (EPDM) was synthesized. This involves photoinduced grafting of maleic anhydride groups on unsaturated sites of EPDM, followed by incorporation of amino terminated HALS. The grafting and functionalization reactions were characterized by FTIR and C-13 NMR spectroscopy. The surface changes upon degradation are studied by SEM. The photostabilizing efficiency of this polymeric HALS was studied and compared with conventional HALS under accelerated weathering conditions. The HALS grafted EPDM showed significantly improved photostabilizing efficiency.
Keywords: EPDM; light induced grafting; Photostabilization; polymeric HALS

Characterization of polydimethylsiloxane rubber upon photochemical, thermal, salt-fog ageings and exposure to acid vapours - Delor-Jestin, Florence; Tomer, N. S.; Singh, R. P.; Lacoste, Jacques (E-Polymers, 2006)
The changes in the chemical structure and the physical properties of a filled crosslinked polydimethylsiloxane rubber were monitored as a function of various ageing factors. The variables included photochemical, thermal, salt-fog ageings and exposure to acid vapours. Unaged and aged samples were studied by IR spectroscopy, hardness measurements, Differential Scanning Calorimetry (DSC) and thermogravimetric analysis (TGA) coupled with IR spectroscopy. No significant oxidation was detected after all ageings, except for nitric acid treatment. The presence of aluminium trihydrate was clearly identified as responsible for the observed chemical changes. Then an important vulnerability of this filled silicone rubber towards the cross-linking reactions provoked by usual ageings was also detected. The DSC-thermoporosimetry measurements of the mesh size distribution gave a comparison of cross-linking densities for each ageing. The complementary analysis with TGA-IR allowed us to differenciate the thermal stability of the formulation after various ageings and to acquire new knowledge about thermal decomposition.

Cross-linking assessment after accelerated ageing of ethylene propylene diene monomer rubber - Tomer, N. S.; Delor-Jestin, Florence; Singh, R. P.; Lacoste, Jacques (Polymer Degradation and Stability, 2007)
The ageing of filled and cross-linked ethylene propylene diene elastomer (EPDM) has been studied under accelerated UV irradiation (lambda >= 290 nm) at 60 degrees C, thermal ageing at 100 degrees C and in nitric acid vapours for different time intervals. Hardness measurements were performed. DSC-thermoporosimetry was used to estimate the mesh size distribution and cross-linking densities for each ageing. The development of functional groups was monitored by ATR spectroscopy. An increase in oxidation with exposure time after the different types of ageing was observed. The thermal stability of EPDM was assessed by TGA and evolved volatile gases were identified using FTIR spectroscopy. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: ageing; EPDM; Oxidation; thermal analysis; thermoporosimetry

Durability of crosslinked polydimethylsyloxanes: the case of composite insulators - Delor-Jestin, Florence; Tomer, Namrata S.; Singh, Raj Pal; Lacoste, Jacques (Science and Technology of Advanced Materials, 2008)
Most applications of silicones are linked to their hydrophobic properties and (or) their high resistance to ageing (e. g. thermal ageing and photoageing). However, when placed in extreme environments, these materials can fail as in the case of epoxy/fiber glass composite powerlines insulators, where crosslinked polymethylsyloxanes (PDMSs) are used as the protective envelope (housing) of the insulator. We report on the behavior of both pure/noncrosslinked PDMSs and typical formulations used in industrial insulators, i.e. containing peroxide crosslinked PDMS, alumina trioxide hydrated (ATH) and silica. Special attention is paid on both (i) the sources of potential degradation and (ii) the best analytical methods that can be applied to the study of very complex formulations. (i) Aside from conventional types of ageing such as photo-ageing and thermal, hydrolytic, and service life ageings, treatments with acidic vapors, plasma and ozone possibly generating species from the reaction of a high electric field with air were also performed, which allowed to accelerate electrical and out-door ageings and to obtain differently aged materials. (ii) Aside from conventional analytical methods of polymer degradation such as FTIR/ATR spectroscopy and SEC, TG, hardness measurements, more specific methods like photo/DSC, TG/IR, thermoporosimetry, resistivity and density measurements were also performed to characterize the chemical and physical evolutions of polymer materials. In particular, it was found that treatment with nitric acid vapor has detrimental effects on the properties of both fire retardants (e. g. ATH) and PDMSs, affecting the hardness and resistivity of the formulated material.
Keywords: composite insulators; durability; PDMS; post-crosslinking; silicone